Competence expected from advanced-level paramedics by emergency medical services managers in Finland: a modified Delphi study - Antti Tanninen; Anne Kouvonen; Hilla Nordquist (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Competence is a critical attribute for paramedics in emergency medical services (EMSs) because of the complex and diverse demands of the prehospital environment. This study aimed to identify and rank the key competencies expected of advanced-level paramedics as perceived by EMS managers. Methods The modified Delphi study included three rounds conducted between October 2022 and June 2023. The panel consisted of 44 EMS managers, all working as superiors in EMS organizations across Finland. Results In Round 1, 44 experts (100% response rate) evaluated 43 claims, with a consensus (≥ 75%) reached on five claims. The open-ended responses generated seven additional claims. In Round 2, 45 claims were reviewed; however, no consensus was reached. In Round 3, the top 15 claims from previous rounds were reevaluated (95% response rate), with assessment of patient conditions via the ABCDE protocol ranking highest. The experts also emphasized patient-centered care, safe environments, and systematic approaches in EMS. Conclusions This study used the Delphi method to identify essential competencies for advanced-level paramedics, emphasizing patient assessment via the ABCDE protocol. This highlights the importance of core skills and nontechnical competencies such as supervision and well-being, stressing the need for continuous updates in paramedic training.